A scoping review of the incentives for promoting the adoption of agroecological practices and outcomes among rice farmers in Vietnam - Ogutu, Sylvester; Mockshell, Jonathan; Minh, Thai Thi; Remans, Roseline (2025)
Recent research and development efforts to achieve sustainable rice production in Vietnam have incorporated agroecological principles and practices. These efforts have come as a result of increasing pressure on food systems to achieve global food security. Growing food demand, rising population, climate change, and natural resources degradation, make it necessary to transform the current production systems towards more sustainable models. Agroecology is being promoted as one of the pathways to transition toward sustainable food production, with broad adoption requiring incentives for farmers. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews guidelines, we conducted a scoping review of 120 articles to understand the incentives applied for promoting agroecological practices, whether and how the incentives promote the adoption of agroecological practices, and their relationship with economic, environmental, and social outcomes among rice farmers in Vietnam. Such in-depth reviews of the role of incentives in the agroecological transition are scarce. Results show that in about 60% of the articles, incentives led to adoption, outcomes (e.g., yield and income gains), or both, suggesting the importance and common use of incentives among rice farmers in Vietnam. Four types of incentives used were market, non-market, regulatory, and cross-compliance. These incentives directly or indirectly influenced outcomes through the adoption of agroecological practices. Market incentives (33%) were relatively more important for directly influencing outcomes, while non-market incentives (50%) were more important for indirectly influencing outcomes. Market, non-market, and regulatory incentives were more associated with the adoption of new agronomic practices, such as farm diversification, improved varieties, and organic agriculture than with other practices, while cross-compliance incentives were more highly associated with adoption of agroforestry. Generally, the incentives used were more associated with economic outcomes (56%), than with environmental (31%), and social (13%) outcomes. Overall, the results show that incentives influence outcomes differently, and a combination of different incentives is required to achieve holistic outcomes.